Occurrence of Helicobacter pylori in saliva from preschool‐age children. Issue 1 (10th September 2014) - Ueda, Jun; Yamaguchi, Akira; Shibasaki, Kohichi
Abstract: Introduction: It is known that initial infection with Helicobacter pylori can occur in children aged 5 years or less, but there have been no studies investigating the period of initial infection. Here, 418 children attending preschool, and their parents, were tested for H. pylori DNA by real‐time PCR using saliva samples in order to infer the period of initial infection of H. pylori . Methods: Subjects took samples of their saliva by chewing on a sterile absorbent cotton roll for 2 minutes, and samples were stored at −80°C until they were examined. DNA was extracted from 100 μl of saliva and was tested for H. pylori DNA using the TaqMan method. Result: The H. pylori DNA detection rate among children was: 4.1% among 3‐year‐olds, 4.9% among 4‐year‐olds, 10.0% among 5‐year‐olds, and 13.3% among 6‐year‐olds. The detection rate thus increased with age, showing a sharp increase from age 4 to 5 years. The rate of H. pylori detection among mothers of H. pylori ‐positive children was 56.2%, which was significantly greater than the rate among mothers of H. pylori ‐negative children (17.2%). Conclusion: These results suggest that initial infection occurs even in children aged under 3 years, and the rise in detection rate between age 4 and 5 years suggests that there is a high risk of H. pylori infection during this period. Furthermore, the finding that the positivity rate was significantly higher among mothers of H. pylori ‐positive children than mothers of H. pylori ‐negative children indicates that mother‐child infection is the most important route.